Notes on the Herbaceous plants of Ayer Hitam Forest Reserve, Puchong, Selangor - G., Rusea; M. D., Bibian; W. K., Soh; Maideen, Haja (Universiti Putra Malaysia Press, 2001)
A survey conducted on the plants of Ayer Hitam Forest Reserve recorded 27 species of herbaceous plants which represented 19 families. From this total, 8 species are recorded for the first time from this forest. Five spesies endemic to Peninsular Malaysia are also found here. This finding has increased the current herb checklist of Ayer Hitam Forest Reserve to 86 species.